Spina Bifida in Iceland: Epidemiology, Health and Well-being among Adults - Marrit Meintema 1964- (2015)
Spina bifida (SB) is one of the most frequent congenital deformities of the neural tube. It is a complex congenital deformity with a variety of complications that require comprehensive multidisciplinary medical care. During the twenty-first century lifestyle-related conditions have been among the leading causes of morbidity and premature death in both developing and developed countries. Because of the limitations and complications associated with SB, individuals with SB are at increased risk for developing lifestyle-related conditions. Aim: The aim of the study was to perform a descriptive epidemiological investigation of the SB population in Iceland and to assess health and well-being of the adult SB population. Methods: The first part of the study was a retrospective study which described the incidence and prevalence of SB between 1972 and 2011; and the mobility, cognitive functioning and the comorbidities children with SB had at the age of five years. The second part of the study was a cross-sectional study and assessed the health and well-being of the adult Icelandic SB population currently living in Iceland, born between 1967 and 1996. Twenty-five participants (69%, age 18-47 years, 9 men and 16 women), took part and answered the survey “Research on the health and well-being of Icelanders in 2012”.Each participant wore an accelerometer for seven days to measure physical activity and kept a physical activity diary. The waist- and hip-circumferences were measured to evaluate the risk of metabolic/lifestyle complications. In the third part of the study, the results of the questionnaire “health and well-being of Icelanders” were compared with the results from a group of Icelandic participants who answered the survey in 2012 (age 18-47 years, n=2159). Results: The incidence of SB has markedly declined in Iceland during the last forty years. At five years of age most of the children with SB could walk, had a low borderline or normal intelligence and the comorbidities were mostly orthopedic impairments, ...